Self-generating interbody fusion cage and preparation method thereof
By combining 3D-printed porous tantalum stents with bioactive piezoelectric ceramics, the problem of insufficient biocompatibility and bone integration capabilities of existing intervertebral fusion device materials is solved, and an efficient intervertebral fusion effect is achieved.
Patent Information
- Application Number
- CN202510460933.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-14
- Publication Date
- 2025-08-19
AI Technical Summary
The existing intervertebral fusion device materials have shortcomings in terms of biocompatibility, osseous integration capability and mechanical strength, resulting in poor fusion rate after implantation, and the existing methods are complex in operation and easy to fall off.
Porous tantalum stents are prepared by 3D printing technology, and bioactive piezoelectric ceramics are combined on it, including barium titanate and hydroxyapatite. They use mechanical forces in the human body to self-generate and promote bone formation, and bioactive piezoelectric ceramics are prepared by high-temperature sintering and polarization treatment.
Self-generating power promotes intervertebral fusion, improves bone graft fusion rate, reduces stress masking effect, enhances biocompatibility and mechanical properties, and promotes the proliferation and differentiation of bone cells.
Smart Images

Figure CN120501924A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the fields of biomedicine and material technology, and in particular to a self-generating intervertebral fusion device and a preparation method thereof. Background Art
[0002] Spinal fusion and internal fixation is a common surgical method for treating degenerative spinal diseases, and its core lies in the effective application of intervertebral fusion devices. Intervertebral fusion devices can provide stability for the upper and lower vertebrae that need to be fused, and can help restore normal intervertebral height and improve bone graft fusion rate. The properties that intervertebral fusion device materials should have include good biocompatibility; good bone conduction ability; good bone induction ability; certain mechanical strength; and good plasticity. The materials currently used in clinical practice for intervertebral fusion devices are mainly polyetheretherketone (PEEK), titanium (Ti) alloys, etc. The main advantages of titanium and titanium alloys are their good biocompatibility and corrosion resistance. However, their excessive mechanical strength can easily cause stress shielding effects, leading to a series of postoperative complications such as fusion device sinking and displacement.
[0003] Compared to titanium and titanium alloy stents, PEEK fusion devices offer radiolucency and an elastic modulus very close to that of cortical bone. Considering their production cost, they remain the most commonly used material for intervertebral fusion devices in clinical practice. However, their relatively poor biocompatibility, hydrophobic surface, and chemical inertness make it difficult to achieve good bone healing during osseointegration. Clinically, fusion rates after PEEK fusion device implantation have been unsatisfactory.
[0004] Patent CN 118267518A discloses a medical copper-doped nano-hydroxyapatite-coated porous tantalum implant material and a preparation method thereof. The preparation method comprises: etching a graphite carbon skeleton with an HCl solution, washing, and drying to obtain a porous carbon skeleton, and placing the skeleton into a vapor deposition reaction chamber; introducing a treatment gas and a reducing gas into the reaction chamber for vapor deposition to deposit a tantalum coating on the surface of the porous carbon skeleton to obtain a porous tantalum metal stent; the treatment gas comprises a tantalum source and a carrier gas; dissolving a copper source, a calcium source, a phosphorus source, and sodium chloride in deionized water, and adjusting the pH to obtain an electrolyte; using the tantalum metal porous stent as a working electrode and graphite as a counter electrode, electrochemical deposition is performed in a pulsed current mode in the electrolyte to deposit a copper-doped nano-hydroxyapatite coating on the surface of the tantalum metal porous stent; and then washing and drying to obtain a medical copper-doped nano-hydroxyapatite-coated porous tantalum implant material having both good bone integration ability and antibacterial properties. However, this method is complicated to operate, and the copper-doped nanohydroxyapatite coating constructed by electrochemical deposition is not only easy to fall off, but also mainly provides antibacterial properties and weak bone integration ability when used as an intervertebral fusion device. Its osteogenic properties are difficult to meet the current needs of intervertebral fusion. Summary of the Invention
[0005] The purpose of the present invention is to provide a self-generating intervertebral fusion device and a preparation method thereof, which can spontaneously promote osteogenesis and intervertebral fusion.
[0006] The objectives of the present invention can be achieved through the following technical solutions: A self-generating intervertebral fusion device, comprising a porous tantalum support and a bioactive piezoelectric ceramic arranged on the porous tantalum support, wherein the bioactive piezoelectric ceramic comprises a bioactive material hydroxyapatite (HA) and a piezoelectric material barium titanate (BTO).
[0007] The intervertebral fusion device of the present invention can actively promote osteogenesis by utilizing the self-generated electrical stimulation of intervertebral stress, and can better meet the current needs of intervertebral fusion.
[0008] Preferably, the upper and lower surfaces of the porous tantalum stent are provided with reserved assembly positions for bioactive piezoelectric ceramics.
[0009] Further preferably, the size of the porous tantalum stent is (12-18) mm*(8-12) mm*(8-12) mm, the size of the bioactive piezoelectric ceramic is (8-12) mm*(5-7) mm*(1.8-2.2) mm, and a piece of bioactive piezoelectric ceramic is provided on the upper and lower surfaces of the porous tantalum stent.
[0010] More preferably, the size of the porous tantalum stent is 15 mm*10 mm*10 mm, and the size of the bioactive piezoelectric ceramic is 10 mm*6 mm*2 mm.
[0011] Further preferably, the upper and lower surfaces of the porous tantalum stent are reserved for assembling sites of bioactive piezoelectric ceramics, and the cross-sectional dimensions thereof are the same as those of the bioactive piezoelectric ceramics.
[0012] Further preferably, after the bioactive piezoelectric ceramic is assembled to the porous tantalum support, the surface is higher than the porous tantalum support or flush with the porous tantalum support.
[0013] More preferably, after the bioactive piezoelectric ceramic is assembled into the porous tantalum support, the surface is 0.01-1 mm higher than the porous tantalum support.
[0014] Preferably, the porous tantalum stent has a rod diameter of 300-400 mm, a pore diameter of 550-650 mm, and a porosity of 75-85%.
[0015] The porous tantalum scaffold of the present invention has excellent performance and can better enhance the adhesion between bones and implants.
[0016] Further preferably, the porous tantalum stent has a rod diameter of 350 mm, a pore diameter of 600 mm, and a porosity of 80%.
[0017] Preferably, the unit coefficient of the porous tantalum stent is 2.200-2.400.
[0018] Further preferably, the unit coefficient of the porous tantalum support is 2.300.
[0019] Preferably, in the bioactive piezoelectric ceramic, the weight ratio of barium titanate to hydroxyapatite is (92-98):(2-8).
[0020] Further preferably, in the bioactive piezoelectric ceramic, the weight ratio of barium titanate to hydroxyapatite is (94-96):(4-6).
[0021] More preferably, in the bioactive piezoelectric ceramic, the weight ratio of barium titanate to hydroxyapatite is 95:5.
[0022] Preferably, the bioactive piezoelectric ceramic grains are circular or nearly circular in shape, with a diameter of 200-400 nm, and there are gaps between the grains.
[0023] A method for preparing the self-generating intervertebral fusion cage comprises the following steps:
[0024] A porous tantalum scaffold is produced by 3D printing, and assembly positions for bioactive piezoelectric ceramics are reserved on the upper and lower surfaces of the porous tantalum scaffold, and the bioactive piezoelectric ceramics are embedded in the assembly positions on the upper and lower surfaces of the porous tantalum scaffold.
[0025] The intervertebral fusion cage of the present invention is made of 3D-printed porous tantalum metal combined with bioactive piezoelectric ceramics.
[0026] Preferably, the porous tantalum stent is made by 3D printing of micron-sized spherical tantalum powder using selective laser melting (SLM) technology.
[0027] Tantalum is a highly promising biomaterial, highly inert and corrosion-resistant. Compared to titanium, tantalum exhibits improved biocompatibility while possessing mechanical properties more closely aligned with cortical bone. Using SLM technology, complex porous tantalum scaffold structures can be 3D printed. Unlike solid tantalum metal, the structure of porous tantalum is more similar to the trabecular structure of cancellous bone. Simultaneously, its elastic modulus and compressive strength decrease with increasing porosity, enabling design to achieve more closely aligned mechanical properties. This structural optimization effectively avoids stress shielding, improves bone graft fusion rates, and provides support for intervertebral fusion.
[0028] Further preferably, the particle size of the tantalum powder is 1-10 μm.
[0029] Preferably, the method for preparing the bioactive piezoelectric ceramic comprises the following steps:
[0030] Nano-hydroxyapatite and nano-barium titanate are mixed and ground to prepare BTO / HA composite material powder, the BTO / HA composite material powder is calcined at 1200-1300°C for 3-5 hours and then cooled to obtain sintered powder, the sintered powder is mixed and ground with a binder, and compacted at 25-35 MPa, and the compacted sample is calcined at 500-600°C for 3-5 hours and at 1200-1300°C for 3-5 hours in sequence to prepare the bioactive piezoelectric ceramic.
[0031] Further preferably, the particle size of the nano-hydroxyapatite is less than 200 nm.
[0032] Further preferably, the particle size of the nano-scale barium titanate is less than 200 nm.
[0033] Further preferably, nano-hydroxyapatite and nano-barium titanate are mixed and ball-milled, isopropyl alcohol and zirconium oxide balls are added during ball milling, the powder-to-ball ratio is 1:(2-4), and the ball milling is carried out at a speed of 250-350 rpm for 5-7 hours.
[0034] More preferably, the binder accounts for 4-6% of the weight of the sintered powder.
[0035] More preferably, the binder accounts for 5% by weight of the sintered powder.
[0036] Further preferably, the adhesive comprises polyvinyl alcohol (PVA).
[0037] Further preferably, the compacted sample is calcined at 500-600°C and 1200-1300°C in sequence to obtain a ceramic sample, and the ceramic sample is polarized in a silicone oil bath at 150-170°C under a DC electric field of 1.5-2.5 kV / mm for 25-35 minutes to obtain the bioactive piezoelectric ceramic.
[0038] More preferably, the bioactive piezoelectric ceramic is obtained by polarizing the ceramic sample in a silicone oil bath at 160° C. for 30 min under a DC electric field of 2 kV / mm.
[0039] Further preferably, nano-hydroxyapatite and nano-barium titanate are mixed and ground to obtain BTO / HA composite material powder, the BTO / HA composite material powder is calcined at 1250°C for 4 hours and then cooled to obtain sintered powder, the sintered powder is mixed and ground with a binder, and compacted at 30 MPa, and the compacted sample is calcined at 550°C for 4 hours and at 1250°C for 4 hours in sequence to prepare the bioactive piezoelectric ceramic.
[0040] Further preferably, the method for preparing the bioactive piezoelectric ceramic comprises the following steps:
[0041] After mixing nano-hydroxyapatite and nano-barium titanate in a preset weight ratio, they were ball-milled for 6 hours, and the mixed BTO / HA composite powder was dried, sieved with a 200-mesh sieve, and allowed to stand for 24 hours. Subsequently, the BTO / HA composite powder was calcined in a muffle furnace at 1250°C for 4 hours, and the sintered powder was compacted with 5wt% polyvinyl alcohol (PVA) adhesive at 30MPa using a hydraulic press. It was then placed in a muffle furnace again and calcined at 550°C for 4 hours to remove the PVA adhesive, and then heated to 1250°C and calcined for 4 hours to obtain a ceramic sample. In order to achieve better piezoelectric performance, the ceramic sample was polarized in a 160°C silicone oil bath under a direct current (dc) field of 2kV / mm for 30 minutes to obtain the final bioactive piezoelectric ceramic.
[0042] An application of the self-generating intervertebral fusion cage is to use the intervertebral fusion cage for human spinal intervertebral fusion.
[0043] Preferably, the following steps are included: removing the diseased intervertebral disc, expanding the intervertebral space to restore physiological height, accurately embedding the intervertebral fusion device and ensuring close fit with the end plate, and implanting bone graft materials such as autologous bone, allogeneic bone or synthetic materials in the middle, and combining internal fixation systems such as pedicle screws to enhance stability when necessary, ultimately promoting bone integration and spinal segment fusion.
[0044] The intervertebral fusion device of the present invention can utilize the mechanical force in the human spine to generate self-electricity and promote intervertebral fusion.
[0045] Bioelectricity is an important physiological activity in the human body. Among them, endogenous piezoelectricity plays an important role in tissue regeneration and physiological processes. Piezoelectric materials are materials that exhibit the piezoelectric effect, that is, they can generate an electric charge in response to applied mechanical stress. Studies have shown that bone is a natural piezoelectric composite material that can convert mechanical stimulation into electrical effects and plays an important role in bone maturation, remodeling, and reconstruction. Therefore, if continuous current stimulation can be given to the intervertebral fusion site to promote the attachment, proliferation, and differentiation of osteoblasts, the success rate of vertebral fusion will be greatly improved.
[0046] Natural bone is the result of tens of thousands of years of evolution and natural selection. Its advantages in mechanical properties, structure, and biofunctionality are difficult to replace with current artificial materials. As the primary inorganic component of human bone, HA is widely used in bone defect repair research. HA is a bioactive ceramic material primarily composed of phosphate and calcium ions. HA has a certain solubility in the human body and can release the calcium and phosphate ions required for bone cell proliferation, thereby participating in in vivo metabolism and promoting intervertebral fusion.
[0047] In this invention, in order to design a scaffold with appropriate microstructure, mechanical properties, and spontaneous osteogenesis, a porous tantalum scaffold was first 3D printed using SLM technology. HA and BTO were then composited by high-temperature sintering to ultimately produce a composite porous tantalum scaffold with a piezoelectric effect. In vitro cell experiments confirmed that it not only promoted the migration and proliferation of bone marrow mesenchymal stem cells (BMSCs), but also exhibited good osteogenic differentiation ability in vitro. Therefore, the porous tantalum scaffold designed in this invention, combined with bioactive piezoelectric ceramics, is a promising intervertebral fusion device.
[0048] Compared with the prior art, the present invention has the following beneficial effects:
[0049] 1. This invention combines piezoelectric materials with a conductive tantalum metal stent. After implantation into the human body, the piezoelectric ceramics located on the upper and lower surfaces of the intervertebral fusion device can continuously utilize the pressure between the human spine to generate electric current, stimulating the proliferation and differentiation of surrounding bone cells, thereby promoting intervertebral fusion.
[0050] 2. This invention combines a 3D-printed porous tantalum scaffold and a bioactive piezoelectric ceramic by inlaying the upper and lower surfaces. The high-temperature sintering and printing method described above offers a simple process for producing an intervertebral fusion device that utilizes internal stress-induced self-generation to promote intervertebral fusion. The device is easy to operate, has controllable composition and structure, and easily optimizes the interface.
[0051] 3. This invention uses SLM technology to 3D print a porous tantalum scaffold with bioactive piezoelectric ceramic binding sites. This porous structure significantly reduces the elastic modulus and strength of the fusion cage. Scanning electron microscopy also reveals that the porous tantalum scaffold has a three-dimensional reticular structure with uniform pores and good interconnectivity, which facilitates cell ingrowth and nutrient exchange.
[0052] 4. The present invention adds HA, the main component of bone, to BTO piezoelectric ceramics. After implantation into the human body, it can not only degrade and release phosphate, calcium ions and other main components of bone formation, but also significantly improve the mechanical properties without almost reducing the piezoelectric performance, and the hydrophilicity is also better.
[0053] 5. The present invention adopts a high-temperature sintering method to prepare BTO / HA composite bioactive piezoelectric ceramics with uniform grain growth, similar grain size, certain size and shape, and gaps between the grains, and at the same time has good mechanical properties.
[0054] 6. After high-voltage polarization, the bioactive piezoelectric ceramics of the present invention have good piezoelectric properties and hydrophilicity, and good interface bonding, which can effectively promote the adhesion and proliferation of BMSCs.
[0055] 7. Compared with existing intervertebral fusion devices, the present invention has the advantages of utilizing the mechanical force in the human body to generate electricity to promote vertebral fusion, matching the mechanical properties of the fusion device contact surface, providing bone formation-related ions, and better interface bonding. BRIEF DESCRIPTION OF THE DRAWINGS
[0056] Figure 1 The following is a flow chart of the preparation and biological verification process of the self-generating intervertebral fusion device of the present invention;
[0057] Figure 2 The schematic diagram and actual diagram of the structure of the self-generating intervertebral fusion device prepared by the present invention;
[0058] Figure 3 This is a SEM photo of the porous tantalum stent prepared in the present invention;
[0059] Figure 4 This is a SEM photo of the bioactive piezoelectric ceramic prepared by the present invention;
[0060] Figure 5 EDS photos and elemental characterization diagrams of the bioactive piezoelectric ceramics prepared in this invention;
[0061] Figure 6 This is a characterization diagram of the mechanical properties test of the bioactive piezoelectric ceramics prepared by the present invention;
[0062] Figure 7 This is a characterization diagram of the piezoelectric properties of the bioactive piezoelectric ceramics prepared by the present invention;
[0063] Figure 8 This is a characterization diagram of the water contact angle (hydrophilicity) of the bioactive piezoelectric ceramics prepared in the present invention;
[0064] Figure 9 This is a photo of BMSCs adhering and growing on the self-powered intervertebral fusion cage of the present invention;
[0065] Figure 10 This is a graph showing the hemolytic activity test results of the self-generating intervertebral fusion device of the present invention;
[0066] Figure 11 This is a graph showing the results of a toxicity test on the extract of the self-generating intervertebral fusion device of the present invention;
[0067] Figure 12 This is a diagram showing the experimental results of the self-generating intervertebral fusion device of the present invention promoting the proliferation of BMSCs;
[0068] Figure 13 This is a diagram showing the experimental results of the self-powered intervertebral fusion device of the present invention promoting the migration of BMSCs;
[0069] Figure 14 This is a diagram showing the experimental results of the self-generating intervertebral fusion device of the present invention promoting the differentiation of BMSCs;
[0070] Figure 15 This is a piezoelectric performance characterization diagram of the bioactive piezoelectric ceramic prepared in Comparative Example 1;
[0071] Figure 16 This is a piezoelectric performance characterization diagram of the unpolarized bioactive piezoelectric ceramic of Comparative Example 2;
[0072] Figure 17 This is a characterization graph of the water contact angle (hydrophilicity) of the unpolarized bioactive piezoelectric ceramic of Comparative Example 2;
[0073] Figure 18 This is a piezoelectric performance characterization diagram of the bioactive piezoelectric ceramic of Comparative Example 3;
[0074] Figure 19 This is a piezoelectric performance characterization diagram of the bioactive piezoelectric ceramic of Comparative Example 4;
[0075] Figure 20 This is a piezoelectric performance characterization diagram of the bioactive piezoelectric ceramic of Comparative Example 5;
[0076] Figure 21 This is a characterization diagram of the water contact angle (hydrophilicity) of the bioactive piezoelectric ceramic of Comparative Example 5. DETAILED DESCRIPTION
[0077] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.
[0078] A method for preparing a self-generating intervertebral fusion device, such as Figure 1 As shown, the following steps are included:
[0079] A porous tantalum scaffold is produced by 3D printing, and assembly positions for bioactive piezoelectric ceramics are reserved on the upper and lower surfaces of the porous tantalum scaffold;
[0080] Hydroxyapatite and barium titanate powders are mixed to prepare BTO / HA composite powders, the BTO / HA composite powders are calcined and then cooled to obtain sintered powders, the sintered powders are mixed with a binder, ground, and then compacted, the compacted sample is first calcined to remove the binder, and then calcined to prepare bioactive piezoelectric ceramics;
[0081] The bioactive piezoelectric ceramics were embedded in the assembly positions of the upper and lower surfaces of the porous tantalum scaffold to obtain Figure 2 The self-generating intervertebral fusion cage is shown.
[0082] The following describes it in detail with reference to specific embodiments.
[0083] Unless otherwise specified, the reagents, methods, instruments and equipment used in the present invention are conventional reagents, methods, instruments and equipment in the art. Unless otherwise specified, the reagents and materials used in the following examples are commercially available.
[0084] Example 1
[0085] A method for preparing a self-generating intervertebral fusion cage, the method comprising the following steps:
[0086] (1) Porous tantalum scaffold: Micron-scale 3D printed spherical tantalum powder (1-10 μm) was SLM-printed using a 3D printer. The dimensions of the porous tantalum scaffold were 15 mm * 10 mm * 10 mm, with the following parameters: rod diameter 350 mm, pore diameter 600 mm, porosity 80%, and reserved assembly areas for bioactive piezoelectric ceramics on the upper and lower surfaces;
[0087] (2) Bioactive piezoelectric ceramics: Nano-scale HA (<200nm) and BTO (<200nm) were mixed in a preset mass ratio and ball-milled in a planetary ball mill for 6 hours to prepare a 95% BTO / 5% HA composite powder material. Specifically, an appropriate amount of zirconia balls was placed in a clean ball mill, and a certain amount of isopropyl alcohol and a certain proportion of HA and BTO powders were added to the ball mill to ensure that the powder-to-ball ratio was approximately 1:3. The planetary ball mill was used for 6 hours at a speed of 300 rpm. The mixed BTO / HA composite powder was dried, sieved with a 200-mesh sieve, and allowed to stand for 24 hours. Subsequently, the BTO / HA composite powder material was calcined in a muffle furnace at 1250°C for 4 hours, with a heating rate of 5°C / min and a cooling rate of 5°C / min. The sintered powder was mixed with 5% PVA binder using a hydraulic press, manually ground in a grinding dish for 30 minutes, sieved with a 200-mesh sieve, and allowed to stand for 24 hours. Finally, the 95% BTO / 5% HA / PVA composite powder material was compacted at 30 MPa to prepare a 10mm*6mm*2mm sample. The compacted sample was placed in a muffle furnace again, first calcined at 550°C for 4 hours to remove the PVA binder, and then heated to 1250°C and calcined for 4 hours to obtain a ceramic sample. Finally, for better piezoelectric performance, the ceramic sample was polarized in a 160°C silicone oil bath under a direct current electric field (dc) of 2 kV / mm for 30 minutes to obtain the final bioactive piezoelectric ceramic;
[0088] (3) Finally, the bioactive ceramic with piezoelectric properties prepared in step (2) is embedded in the preset sites on the upper and lower surfaces of the 3D printed porous tantalum scaffold in step (1) for bonding.
[0089] Example 2
[0090] A method for preparing a self-generating intervertebral fusion cage, the method comprising the following steps:
[0091] (1) Porous tantalum scaffold: Micron-scale 3D printed spherical tantalum powder (1-10 μm) was SLM-printed using a 3D printer. The dimensions of the porous tantalum scaffold were 12 mm*8 mm*8 mm, with the following parameters: rod diameter 300 mm, pore diameter 550 mm, porosity 75%, unit coefficient 2.200, and reserved assembly areas for bioactive piezoelectric ceramics on the upper and lower surfaces.
[0092] (2) Bioactive piezoelectric ceramics: Nano-scale HA (<200nm) and BTO (<200nm) were mixed in a preset mass ratio and ball-milled in a planetary ball mill for 7 hours to prepare a 92% BTO / 8% HA composite powder material. Specifically, an appropriate amount of zirconia balls was placed in a clean ball mill, and a certain amount of isopropyl alcohol and a certain proportion of HA and BTO powders were added to the ball mill to ensure that the powder-to-ball ratio was approximately 1:2. The planetary ball mill was used for 7 hours at a speed of 250 rpm. The mixed BTO / HA composite powder was dried, sieved with a 200-mesh screen, and allowed to stand for 24 hours. Subsequently, the BTO / HA composite powder was calcined in a muffle furnace at 1200°C for 5 hours, with a heating rate of 5°C / min and a cooling rate of 5°C / min. The sintered powder was mixed with 4% PVA binder using a hydraulic press, manually ground in a grinding dish for 30 minutes, sieved with a 200-mesh sieve, and allowed to stand for 24 hours. Finally, the 92% BTO / 8% HA / PVA composite powder material was compacted at 25 MPa to prepare a sample of 8mm*5mm*1.8mm. The compacted sample was placed in a muffle furnace again, first calcined at 500°C for 5 hours to remove the PVA binder, and then heated to 1200°C and calcined for 5 hours to obtain a ceramic sample. Finally, for better piezoelectric performance, the ceramic sample was polarized in a 150°C silicone oil bath under a direct current electric field (dc) of 2.5kV / mm for 25 minutes to obtain the final bioactive piezoelectric ceramic;
[0093] (3) Finally, the bioactive ceramic with piezoelectric properties prepared in step (2) is embedded in the preset sites on the upper and lower surfaces of the 3D printed porous tantalum scaffold in step (1) for bonding.
[0094] Example 3
[0095] A method for preparing a self-generating intervertebral fusion cage, the method comprising the following steps:
[0096] (1) Porous tantalum scaffold: Micron-scale 3D printed spherical tantalum powder (1-10 μm) was SLM-printed using a 3D printer. The dimensions of the porous tantalum scaffold were 18 mm*12 mm*12 mm, with the following parameters: rod diameter 400 mm, pore diameter 650 mm, porosity 85%, unit coefficient 2.400, and assembly sites for bioactive piezoelectric ceramics were reserved on the upper and lower surfaces.
[0097] (2) Bioactive piezoelectric ceramics: Nano-scale HA (<200nm) and BTO (<200nm) were mixed in a preset mass ratio and ball-milled in a planetary ball mill for 5 hours to prepare a 98% BTO / 2% HA composite powder material. Specifically, an appropriate amount of zirconia balls was placed in a clean ball mill, and a certain amount of isopropyl alcohol and a certain proportion of HA and BTO powders were added to the ball mill to ensure that the powder-to-ball ratio was approximately 1:4. The planetary ball mill was used for 5 hours at a speed of 350 rpm. The mixed BTO / HA composite powder was dried, sieved with a 200-mesh sieve, and allowed to stand for 24 hours. Subsequently, the BTO / HA composite powder material was calcined in a muffle furnace at 1300°C for 3 hours, with a heating rate of 5°C / min and a cooling rate of 5°C / min. The sintered powder was mixed with 6% PVA binder using a hydraulic press, manually ground in a grinding dish for 30 minutes, sieved with a 200-mesh sieve, and allowed to stand for 24 hours. Finally, the 98% BTO / 2% HA / PVA composite powder material was compacted at 35 MPa to prepare a 12mm*7mm*2.2mm sample. The compacted sample was placed in a muffle furnace again, first calcined at 600°C for 3 hours to remove the PVA binder, and then heated to 1300°C and calcined for 3 hours to obtain a ceramic sample. Finally, for better piezoelectric performance, the ceramic sample was polarized in a 170°C silicone oil bath under a direct current electric field (dc) of 1.5 kV / mm for 35 minutes to obtain the final bioactive piezoelectric ceramic;
[0098] (3) Finally, the bioactive ceramic with piezoelectric properties prepared in step (2) is embedded in the preset sites on the upper and lower surfaces of the 3D printed porous tantalum scaffold in step (1) for bonding.
[0099] Performance testing:
[0100] The porous tantalum stent and bioactive piezoelectric ceramics prepared in Example 1 were subjected to SEM characterization, mechanical property testing, piezoelectric property testing, hydrophilicity testing, biocompatibility testing, hemolysis testing, extract toxicity testing, proliferation promoting performance testing, migration promoting performance testing, and osteodifferentiation promoting performance testing. Specifically:
[0101] 1. SEM characterization
[0102] The morphology of the porous tantalum scaffold and the cross-section of the bioactive piezoelectric ceramics were characterized by scanning electron microscopy (Sigma 300). The distribution of each element in the bioactive piezoelectric ceramics was characterized by energy dispersive spectrometer (Sigma 300). Figure 3 It can be seen that the porous tantalum scaffold has a three-dimensional network structure with uniform pores and good intercommunication, which is conducive to cell growth and nutrient exchange. At the same time, high-resolution scanning electron microscope images also show that the scaffold surface is relatively rough, which is conducive to cell migration and adhesion. For bioactive piezoelectric ceramics, Figure 4 It can be observed that after sintering, the grains grow relatively evenly, the grain sizes are similar, there is no excessive growth of grains, the grain shape is round or nearly round, the diameter is basically 200-400nm, and there are gaps between the grains. At the same time, Figure 5 It can be observed that the cross section of the bioactive piezoelectric ceramics characterized the elements Ba, Ti, Ca, P, and O, proving that HA and BTO were well sintered together.
[0103] 2. Mechanical properties test
[0104] Considering that bioactive piezoelectric ceramics are positioned closer to the upper and lower vertebral endplates during intervertebral fusion surgery, the mechanical properties of bioactive piezoelectric ceramics were measured using a three-point compression fracture test. The tests were performed using a tension-compression testing machine (HY-940FS). The three-point compression fracture test was performed at a constant loading rate of 3.0 mm / min until failure. All specimens were preloaded with 2 N before the start of the test. The flexural modulus and maximum yield stress were calculated using linear elastic beam theory.
[0105] E=k*L 3 / 4*b*d 3
[0106] ρ=3*F*L / 2*b*d 2
[0107] Where b and d are the width and thickness of the sample, 6 mm and 2 mm, respectively. L is the lower span of the sample, set to 6 mm in this study. F is the maximum force at fracture, in Newtons. k is the maximum slope of the stress-displacement curve before any local maximum on the curve.
[0108] Figure 6 The results show that the maximum compressive stress of 95% BTO / 5% HA bioactive piezoelectric ceramics after sintering is 269.64±50.69 MPa and the elastic modulus is 2230.43±269.64 MPa, which can meet the mechanical strength requirements of intervertebral fusion cages.
[0109] 3. Piezoelectric performance test
[0110] The bioactive piezoelectric ceramics were connected to the circuit via copper wires and fixed with insulating tape. A modal exciter (SA-JZ020) was used to apply a force of 6 kPa to the sample surfaces at different proportions, and an oscilloscope (TBS1102X) was used to collect the open-circuit voltage. Figure 7 The graph shows the piezoelectric performance test results of the bioactive piezoelectric ceramic prepared according to Example 1. It can be seen that the open circuit voltage measured is about 11V.
[0111] 4. Hydrophilic performance test
[0112] The surface hydrophilicity of bioactive piezoelectric ceramics was measured at room temperature and atmospheric pressure using a contact angle meter (SDC-350). Deionized water was used as the test liquid, and the volume of each drop of liquid was controlled to 2 ml using a syringe. A photo was taken when the liquid was dropped on the sample surface, and again after 2 seconds and 10 seconds. Figure 8 As shown in the figure, the angle of the bioactive piezoelectric ceramic is about 52° at the moment of contact with the water droplet, and then completely disappears within 10 seconds, proving that it has good hydrophilicity, which is conducive to the effective transfer of body fluids inside the material, better interaction with the surrounding bone tissue, and thus promoting bone integration.
[0113] 5. Biocompatibility testing
[0114] The scaffold's cytocompatibility was assessed using live / dead cell staining. BMSCs were co-cultured with the bioactive piezoelectric ceramic-incorporated scaffold for 3 days. After washing with PBS, cells were stained using a Calcein / PI cell viability and cytotoxicity assay kit. Fluorescence images of BMSCs were recorded using an inverted fluorescence microscope (IX2-ILL30). Figure 9 The green fluorescence represents BMSCs, which can be seen to be well adhered to the scaffold, proving that the designed composite piezoelectric ceramic porous tantalum scaffold has good biocompatibility.
[0115] 6. Hemolysis performance test
[0116] The Ta scaffold and the tantalum scaffold combined with bioactive piezoelectric ceramics were immersed in the prepared 4% red blood cell suspension, with ddH20 and normal saline as positive and negative controls, respectively. They were co-cultured at 37°C for 4 hours, and the OD at 540 nm was measured using a microplate. Figure 10 Graph showing the results of the hemolysis performance test. It can be seen from the graph that the self-powered intervertebral fusion cage exhibits a low hemolysis rate (<3%) and can be considered non-toxic and safe (it is generally believed that the hemolysis rate is <5%).
[0117] 7. Extract toxicity test
[0118] The prepared self-powered intervertebral fusion device was sterilized and placed in serum-free MEM-α culture medium at 37°C for 72 hours to obtain an extract. BMSCs were cultured in the prepared extract medium and normal culture medium for one and two days, respectively. After incubation with CCK-8 solution for 2 hours, the absorbance at 450 nm was measured on a microplate reader to assess cytotoxicity. Figure 11 The results of the extract toxicity test are shown. As can be seen from the figure, after one and two days of co-culture, the absorbance of the self-generating intervertebral fusion device group did not show significant changes compared to the control group. While the cell viability of the control group was set at 100%, the cell viability of the self-generating intervertebral fusion device group exceeded 90%, falling within the cytotoxicity level 0 range of the biological evaluation standards for medical materials. Hemolysis tests and extract experiments demonstrate that the self-generating intervertebral fusion device prepared by this invention has good biocompatibility and is non-toxic to cells, indicating its potential for further research as an implantable material.
[0119] 8. Proliferation-promoting performance test
[0120] BMSCs were co-cultured with a scaffold incorporating bioactive piezoelectric ceramics. Ultrasound was used to stimulate the piezoelectric material to simulate spinal stress and generate electrical stimulation. The proliferation of cells in the scaffold was assessed using CCK-8 assay after 1, 3, and 5 days of incubation. Figure 12 The results of the proliferation-promoting performance test are shown in the figure. After one day of co-culture, there was almost no significant difference in cell number between the groups. After three and five days of co-culture, the cell number in the self-powered interbody fusion device group was significantly higher than in the other five groups. The absorbance measurement results of the CCK-8 assay at 450nm were generally consistent with those of the live-dead staining.
[0121] 9. Migration performance test
[0122] After BMSCs were plated, they were scratched with a 200 μL pipette tip. Then, the scaffolds combined with bioactive piezoelectric ceramics were directly co-cultured with BMSCs according to the groups for 24 hours. The scaffolds were stained with Calcein-AM / PI kit at room temperature for 30 minutes, and the distance of the scratches was observed under a fluorescence microscope to evaluate the migration-promoting performance of the scaffolds. Figure 13 The results showed that compared with the other five groups, the self-generating intervertebral fusion device group had a stronger ability to promote cell migration after 24 hours.
[0123] 10. Osteodifferentiation performance test
[0124] The alkaline phosphatase (ALP) activity assay was used to analyze the effect of the scaffold combined with bioactive piezoelectric ceramics on the early osteogenic differentiation of cells. BMSCs were incubated with the scaffold for 7 days and 14 days. ALP activity was then determined using a BCIP / NBT alkaline phosphatase colorimetric kit, and the stained BMSCs were observed using an inverted research microscope (DMI4000). Figure 14 As shown, on days 7 and 14, ALP staining was significantly darker in the self-powered interbody fusion device group. Calculation of the color area in each group revealed that the self-powered interbody fusion device group had significantly higher staining compared to the other five groups, with statistically significant differences (P < 0.05). Therefore, the self-powered interbody fusion device has the potential to promote osteogenic differentiation of BMSCs, which may enhance intervertebral fusion.
[0125] Comparative Example 1
[0126] Compared with Example 1, the bioactive piezoelectric ceramics used in this comparative example are bioactive piezoelectric ceramics that have not been pre-sintered at 550°C, and other conditions remain unchanged. Figure 15 It can be seen that Comparative Example 1 exhibits poor piezoelectric performance (about 4 V).
[0127] Comparative Example 2
[0128] The bioactive piezoelectric ceramics used in this comparative example are unpolarized bioactive piezoelectric ceramics. Under the same sintering conditions as in Example 1, the hydrophilicity and piezoelectric properties of the unpolarized piezoelectric ceramics were verified. Figure 16 、 17 As shown in the figure, under the same sintering conditions, the unpolarized piezoelectric ceramics only exhibit an open circuit voltage of about 3V and a water contact angle of about 90° at the moment of contact.
[0129] Comparative Example 3
[0130] The bioactive piezoelectric ceramic used in this comparative example is a bioactive piezoelectric ceramic with a weight ratio of 80% BTO and 20% HA. Under the same sintering conditions as in Example 1, the piezoelectric performance of the bioactive piezoelectric ceramic with 80% BTO and 20% HA was verified. Figure 18 As shown in Figure 2, the bioactive piezoelectric ceramics with 80% BTO and 20% HA only exhibit an open circuit voltage of about 2.5 V. Figure 6 As shown, Comparative Example 3 exhibited a maximum compressive strength of approximately 430 kPa and an elastic modulus of approximately 2750 kPa. Although the mechanical test results of Comparative Example 3 were comparable to those of Example 1, its piezoelectric performance was too low to effectively promote bone proliferation and bone integration in the intervertebral fusion area.
[0131] Comparative Example 4
[0132] The bioactive piezoelectric ceramic used in this comparative example is a bioactive piezoelectric ceramic with a weight ratio of 90% BTO and 10% HA. Under the same sintering conditions as in Example 1, the piezoelectric performance of the bioactive piezoelectric ceramic with 90% BTO and 10% HA was verified. Figure 19 As shown in Figure 2, the bioactive piezoelectric ceramics with 90% BTO and 10% HA only exhibit an open circuit voltage of about 7.5 V. Figure 6 As shown, Comparative Example 4 exhibited a maximum compressive strength of approximately 275 kPa and an elastic modulus of approximately 2250 kPa. The mechanical testing of Comparative Example 4 was essentially the same as that of Example 1, but its piezoelectric performance was significantly inferior to that of Example 1 (7.5 V < 11 V), potentially hindering its ability to effectively promote bone proliferation and bone integration in the intervertebral fusion area. Overall, Comparative Example 4 was inferior to Example 1 in terms of all performance characteristics.
[0133] Comparative Example 5
[0134] The bioactive piezoelectric ceramic used in this comparative example is a bioactive piezoelectric ceramic with a weight ratio of 100% BTO. Under the same sintering conditions as in Example 1, the piezoelectric performance of the bioactive piezoelectric ceramic with 100% BTO was verified. Figure 20 、 21 As shown in FIG, although the 100% BTO bioactive piezoelectric ceramic exhibits an open circuit voltage of about 13 V, slightly higher than that of Example 1, its hydrophilicity is poor. At the moment when the water droplet contacts the 100% BTO bioactive piezoelectric ceramic (0 s), it exhibits a water contact angle of about 90°. Figure 6 As shown, Comparative Example 5 only exhibits a maximum compressive strength of about 140 kPa and an elastic modulus of about 2250 kPa, which makes it difficult to be used as a bioactive piezoelectric ceramic implanted in an intervertebral fusion cage.
[0135] This invention provides a method for preparing an intervertebral fusion device that utilizes stress-induced self-generation to promote intervertebral fusion. This method effectively combines the excellent biocompatibility of tantalum metal and the piezoelectric properties of bioactive piezoelectric ceramics with the osteogenic properties of in situ release of osteogenesis-related ions. The porous tantalum scaffold is 3D-printed using SLM technology, which helps reduce the elastic modulus of the intervertebral fusion device and mitigate stress shielding. Furthermore, BTO and HA ceramic powders are aggregated through high-temperature sintering, filling the gaps reserved in the tantalum scaffold. This allows for the in situ release of osteogenesis-related ions and utilizes the self-generated electricity from stress within the spine to promote intervertebral fusion and osseointegration.
[0136] The above description of the embodiments is intended to facilitate understanding and use of the invention by those skilled in the art. It will be apparent that those skilled in the art can readily make various modifications to these embodiments and apply the general principles described herein to other embodiments without requiring inventive effort. Therefore, the present invention is not limited to the above-described embodiments. Improvements and modifications made by those skilled in the art based on the disclosure of the present invention, without departing from the scope of the present invention, should be within the scope of protection of the present invention.
Claims
1. A self-generating intervertebral fusion cage, characterized in that: The invention comprises a porous tantalum support and a bioactive piezoelectric ceramic arranged on the porous tantalum support. The bioactive piezoelectric ceramic contains hydroxyapatite and barium titanate. The weight ratio of the barium titanate to the hydroxyapatite is (92-98): (2-8).
2. The self-generating intervertebral fusion cage according to claim 1, characterized in that: The upper and lower surfaces of the porous tantalum stent are reserved for assembling positions of bioactive piezoelectric ceramics.
3. The self-generating intervertebral fusion cage according to claim 2, characterized in that: The size of the porous tantalum stent is (12-18) mm*(8-12) mm*(8-12) mm, the size of the bioactive piezoelectric ceramic is (8-12) mm*(5-7) mm*(1.8-2.2) mm, and a piece of bioactive piezoelectric ceramic is provided on the upper and lower surfaces of the porous tantalum stent.
4. The self-generating intervertebral fusion cage according to claim 1, characterized in that: The porous tantalum support has a rod diameter of 300-400 mm, a pore diameter of 550-650 mm, and a porosity of 75-85%.
5. The self-generating intervertebral fusion cage according to claim 1, characterized in that: In the bioactive piezoelectric ceramic, the weight ratio of barium titanate to hydroxyapatite is (94-96): (4-6).
6. A method for preparing the self-generating intervertebral fusion cage according to any one of claims 1 to 5, characterized in that: The following steps are involved: A porous tantalum scaffold is produced by 3D printing, and assembly positions for bioactive piezoelectric ceramics are reserved on the upper and lower surfaces of the porous tantalum scaffold, and the bioactive piezoelectric ceramics are embedded in the assembly positions on the upper and lower surfaces of the porous tantalum scaffold.
7. The method for preparing a self-generating intervertebral fusion cage according to claim 6, characterized in that: The porous tantalum stent is produced by 3D printing of micron-sized spherical tantalum powder using selective laser melting technology, and the particle size of the tantalum powder is 1-10 μm.
8. The method for preparing a self-generating intervertebral fusion cage according to claim 6, characterized in that: The preparation method of the bioactive piezoelectric ceramic comprises the following steps: Nano-hydroxyapatite and nano-barium titanate are mixed and ground to prepare BTO / HA composite material powder, the BTO / HA composite material powder is calcined at 1200-1300°C for 3-5 hours and then cooled to obtain sintered powder, the sintered powder is mixed and ground with a binder, and compacted at 25-35 MPa, and the compacted sample is calcined at 500-600°C for 3-5 hours and at 1200-1300°C for 3-5 hours in sequence to prepare the bioactive piezoelectric ceramic.
9. The method for preparing a self-generating intervertebral fusion cage according to claim 8, characterized in that: The particle size of the nano-hydroxyapatite and nano-barium titanate is less than 200 nm; The nano-hydroxyapatite and nano-barium titanate were mixed and ball-milled, and isopropyl alcohol and zirconium oxide balls were added during the ball milling, with a powder-to-ball ratio of 1:(2-4), and the ball milling was carried out at a speed of 250-350 rpm for 5-7 hours; The binder accounts for 4-6% of the weight of the sintered powder.
10. The method for preparing a self-generating intervertebral fusion cage according to claim 8, characterized in that: The compacted sample is calcined at 500-600° C. and 1200-1300° C. in sequence to obtain a ceramic sample, and the ceramic sample is polarized in a silicone oil bath at 150-170° C. under a DC electric field of 1.5-2.5 kV / mm for 25-35 minutes to obtain the bioactive piezoelectric ceramic.
Citation Information
Cited By
Biocompatible material for bionic porous interbody fusion cage and preparation method
CN121570639A
Bionic interbody fusion cage with piezoelectric multifunctional coating
CN122075195A
Biomimetic intervertebral fusion cage with piezoelectric multifunctional coating
CN122075195B